Correlation and Path Analysis Studies in Groundnut under Different Dates of Sowing - Venkataravana P.; Sowjanya, B. A.; Priyadarshini, S. K. (Research Advances and Challenges in Agricultural Sciences Vol. 5, 2024)
Research on the genotypic and phenotypic associations among agricultural crop traits can be used to design, evaluate, and develop selection criteria for desirable traits. Yield is a complex quantitative trait largely influenced by the environment. Direct selection for grain yield is less efficient in improving groundnut productivity. The selection efficiency can be enhanced by exploiting the relationship between yield and its related traits. In the present study strong positive association was noticed between pod yield per plant and kernel yield per plant, oil yield per plant and significant and negative association with late leaf spot severity and rust incidence irrespective of the environments. Pod yield was also correlated with 100-kernel weight, plant height and oil content in environment III. The magnitude and direct association of pod yield with other characters varied from environment to environment. Inter correlation estimates for yield components revealed that plant height, 100-kernel weight, kernel yield per plant, oil yield per plant, late leaf spot severity, number of matured pods per plant, harvest index and plant height were significantly associated with one another and also with pod yield per plant which indicated that these characters were important components for improvement of pod yield in groundnut. This indicated that selection of genotypes based on oil yield per plant and kernel yield per plant is advantageous than the other characters. The direct effect of kernel yield per plant in all the three environments followed by shelling percentage, rust incidence, oil yield per plant, number of branches per plant in environment I and plant height in environment I and III. The direct effect of other characters fluctuated between negative and positive values indicating the influence of environment on these traits.